Household Savings and Income Distribution in Mexico - Orazio P. Attanasio; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1998)
Following the 1994 financial crisis, the rate of saving of the Mexican economy fell from 21. 7 percent to 19. 8 percent of GDP. The decline was associated with a reduction in the rate of external saving from 6. 9 to 0. 5 percent between 1994 and 1995. The overall reduction was not more dramatic because it was almost fully compensated by an increase in private saving from 11. 3 percent to 15 percent of GDP during these years.
Keywords: 330; Sparen; Privater Haushalt; Lebenszyklus; Einkommensverteilung; Mexiko